(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Sinus Histiocytosis/Rosai-Dorfman Disease (RDD) are benign, rare proliferative disorder caused by over production and accumulation of specific type of white blood cell (Phagocytic Histiocyte) in the lymph nodes of the body. Here, lymphadenopathy mostly painless and commonly found in the neck (cervical) but may occur in other areas of the body such as skin, lung, central nervous system, kidney (less than 5%). Predominantly it affects the young age group of children, adolescents or young adults. In spite of spontaneous remissions, treatment strategies can be different according to involvement and severity (RDD- Seldom life threatening disease). Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 176-178